A Revista Veja e o caso do menino Bernardo : um olhar da semiótica discursiva sobre uma reportagem - Schallemberger, Rafaelly Andressa (2015)
This research focuses on the enunciative strategies used by the magazine Veja in producing its reporting. Our objective is to analyze the enunciative strategies and understand the effect on meaning arising from how verbal and non-verbal resources are joined together in building a text that aids in bonding the individual enunciated to the vehiculated discourse, turning him or her into a regular consumer of the magazine. The corpus is a syncretic text, an article from the printed edition of Veja titled "He cried out, but there was no time". This analysis has its theoretical basis in Discursive Semiotics. The choice for this theoretical-applied approach is justified by the fact that Discursive Semiotics has to do with the study of elements of the textual surface which converge in persuading the reader. The guiding theoretical approach is basically enunciative-discursive, supported in Greimas (2013, 2014) and in other scholars of the subject, like Fiorin (1996, 1997, 2006, 2008, 2012), Barros (2002, 2003, 2005, 2012) and Gomes (2005, 2007, 2008, 2009). From the perspective of journalistic discourse, Hernandes stands out (2004, 2006, 2009) and, with respect to socio-ideological formation, Bakhtin (2011, 2014). The methodological procedures are a bibliographic and qualitative search, with analysis of the selected corpus. As to results, we verified that in the article analyzed various resources are used to sweep the reader away. These resources can be divided into two large groups, those of rational order (doing-knowing) and those of emotional order (doing-feeling). In the first group, we observe the resources of actorialization, anchoring, the delegation of voices in direct discourse to the actors of the enunciated material, the objectivity and neutrality on the part of the narrator who enunciates himself in the third person (generic coercions in the reporting category). In the second group, we show elements of emotional order, like the use of photographs, typeface, diagramming, captions, certain linguistic choices like the use of adjectives, tenses (narrator as well as interlocutors), use of person category by the interlocutors (1st or 3rd), elements which move the reader to share in the feelings of the interlocutor. The use of all these resources makes the reader want to buy the magazine, not only for information (want-know), but also to feel (want-feel). In addition, the narrative structure of the text is reminiscent of fairy tales, like Cinderella and Snow White, which constitutes an archetype of narrative with which the reader identifies, insofar as these arouse crystalized memories. It is evident, then, that elements concerning the discursive level and also the narrativity implied in the text constitute strategies designed to bond the reader to the vehiculated discourse